Doctor-Patient Communication A Requisite for Better Medication History Taking: Insight from Sudan - Elamin, Maram M.; Ahmed, Kannan O.; Saeed, Osman K.; Hilali, Mahmoud; Yousif, Mirghani (African Pharmaceutical Journal, 2022)
Despite the awareness of doctors about the significance of obtaining a comprehensive medication history for patients, they often neglect this in their practice, resulting in an incomplete patient medication list. The study aimed to investigate the role of communication skills as a crucial part of optimal pharmacotherapy. An observational, cross-sectional study was carried out at internal medicine department in a tertiary hospital, Wad Medani, Sudan.  The research instrument was a form involved a checklist rating a doctor’s performance during the medical encounters. Among 94 medical doctors, 51% were males and 6.15 (SE) was the average years of experience. About 13% of participants received under-graduation training in communication skills, while 21% had it after post-graduation. Concerning communication skills evaluation, 61% of specialists, 29% of registrars, and 7% of house officers reported an excellent performance. Gender and doctors’ ranking in a medical team had a significant role in communication skills (P-value <0.05) with an overall adjusted R 2 of 0.339. Specialists were the most knowledgeable and skillful in obtaining structured medication history; 67% reported an excellent performance. Communication skills had a remarkable impact in getting patient medication history (P-value: <0.05) with an overall adjusted R 2 of 0. 763.The study concluded that; gender and doctors’ ranking in the medical team were the main predictors for doctors to be a good communicator. Communication skills have a significant role in medication history taking. There was a gap in knowledge and training in communication skills among internal medicine doctors specifically, “house officers.” This gap negatively contributed to obtaining a comprehensive patient medication history.